Emergence of Q fever - E Angelakis; D Raoult (Tehran University of Medical Sciences, 2011)
Q fever is a worldwide zoonosis with many acute and chronic manifestations caused by the pathogen Coxiella burnetii. Farm animals and pets are the main reservoirs of infection, and transmission to human beings is mainly accomplished through inhalation of contaminated aerosols. Persons at greatest risk are those in contact with farm animals and include farmers, abattoir workers, and veterinarians. The organs most commonly affected during Q fever are the heart, the arteries, the bones and the liver. The most common clinical presentation is an influenza-like illness with varying degrees of pneumonia and hepatitis. Although acute disease is usually self-limiting, people do occasionally die from this condition. Endocarditis is the most serious and most frequent clinical presentation of chronic Q fever. Vascular infection is the second most frequent presentation of Q fever. The diagnosis of Q fever is based on a significant increase in serum antibody titers. The treatment is effective and well tolerated, but must be adapted to the acute or chronic pattern with the tetracyclines to be considered the mainstay of antibiotic therapy. For the treatment of Q fever during pregnancy the use of long-term cotrimoxazole therapy is proposed.